Sweet heat : a novel - Babalola, Bolu (Honey & spice, 2025)
"Two exes. One summer wedding. Zero chance of escaping the heat...Twenty-eight-year-old Kiki Banjo hosts the popular podcast The HeartBeat, solving romantic conundrums and dishing out life advice. But behind the mic, career setbacks and a devastating breakup have left her hanging on by a thread. As she's preparing to be the Maid of Honor in her best friend's wedding, everything starts to unravel, and Kiki is left wondering if she ever had the answers. Then Kiki finds herself face-to-face with the Best Man, her ex-boyfriend, Malakai--the smooth-talking, absurdly handsome, annoyingly perceptive man who stole her heart and then shattered it. While Kiki's approaching rock bottom, Malakai's been on the rise as a filmmaker, and now they have no choice but to play nice until the wedding is over. Both are hell-bent on ignoring the smoldering chemistry between them, but as they navigate the chaos of wedding plans, career ambitions, and Kiki's growing fears about the future, they can't ignore the spark that's only getting hotter." --